Strengthening Cultural Care Attitudes through Ethnoscience-Based Physics Learning: A Quasi-Experimental Study with Pre-Service Teachers - Ika Kartika; Faridah Lisa Supian (Equator Science Journal, 2026)
This study examined differences in the improvement of cultural care attitudes among pre-service physics teachers who participated in three instructional conditions within ethnoscience-based physics education. The study employed a quasi-experimental pretest-posttest design involving 270 participants from three teacher education institutions in Yogyakarta, Indonesia, who were distributed across one experimental group and two control groups. The experimental group received physics instruction that positioned ethnoscience and local cultural resources as central learning contexts, whereas the two control groups experienced alternative instructional conditions with less explicit integration of local cultural resources. Cultural care attitudes were measured using an instrument developed and validated in a previous study. Data were analysed using descriptive statistics, paired-samples t tests, ANCOVA with pretest as a covariate, one-way ANOVA on gain scores, and additional cross-campus analyses. The findings showed that all groups improved significantly from pretest to posttest, but the experimental group demonstrated the strongest improvement and the highest adjusted posttest mean after baseline differences were controlled. Pairwise comparisons confirmed that the experimental group outperformed both control groups, while the group by campus interaction was not significant. These findings suggest that different instructional conditions were associated with different affective outcomes and that ethnoscience-based physics learning appeared to support culturally oriented dispositions among pre-service physics teachers.